Analisa Produktivitas dengan Metode POSPAC dan Multi Factor Productivity Measurement Model (MFPMM) (Studi Kasus: Bengkel Mega Teknik, Sidoarjo) - basuki hm, gatot; Arrizal, Arsy (Journal of Research and Technology, 2024)
Productivity is one aspect that is influential and important in the development process of a company. Bengkel Mega Teknik Sidoarjo is a company that manufactory heaters. This study measured productivity using the POSPAC method and the MultiMulti-Factor Factor Productivity Measurement Model (MFPMM) for 2 periods. The results of the POSPAC method showed that production IP decreased by 0.59%; organizational IP decreased by 0.99%; IP sales decreased by 4.84%; Product IP decreased by 1.57%; Labor IP increased by 3.23%; The capital IP decreased by 0.42%. The calculation results of the MFPMM method show that the company's productivity has decreased by 0.5897% which can make the company experience a profit loss of Rp. 10,134,731.68. Proposed improvements to increase productivity are scheduling shipments, regulating energy use according to production needs, selecting raw materials at a cost that is not too expensive with the same quality, conducting work briefings for workers, checking machines regularly, and carrying out cleaning. workplace routinely and effective machine arrangement.